Promoting Gender Inclusion in Computing: An Experience Report on a National Web Development School for Girls - Lauriano, Thaís; Marques, Brena; Garcés, Lina (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2025)
Female representation remains low in undergraduate programs and research related to STEM fields, with women accounting for only an estimated 15% of the sector in Brazil as of 2022. Nevertheless, one factor contributing to the increased participation of women in STEM programs has been the implementation of strategies focused on strengthening girls’ mathematical and scientific foundations during childhood and adolescence. Therefore, aiming to overcome the economic and societal barriers that school-age girls face in accessing this kind of knowledge, the Web Development School for Girls course was developed to promote interest, skills development, and self-confidence among participants, encouraging them to pursue careers in STEM. The initiative was national and conducted fully online, featuring weekly lessons and assessment activities, daily mentoring sessions, and the application of project-based learning, which placed students at the center of the learning process. This program was explicitly aligned with the Sustainable Development Goals (SDGs 4, 5, and 10). The program demonstrated the effectiveness of the PBL methodology through the quality and complexity of the final web projects delivered by the students. While successful in its pedagogical goals, the initiative encountered key limitations, including a high dropout rate of 53.6%. It is concluded that strengthening engagement strategies, such as integrating more frequent live or face-to-face sessions, and refining administrative processes are essential for improving retention in future editions of the school.